2001
DOI: 10.1021/es001873w
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Perfluorooctane Sulfonate in Marine Mammals

Abstract: Perfluorooctane sulfonate (PFOS) is a perfluorinated molecule that has recently been identified in the sera of nonindustrially exposed humans. In this study, 247 tissue samples from 15 species of marine mammals collected from Florida, California, and Alaskan coastal waters; and northern Baltic Sea; the Arctic (Spitsbergen); and Sable Island in Canada were analyzed for PFOS. PFOS was detected in liver and blood of marine mammals from most locations including those from Arctic waters. The greatest concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
301
8
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 475 publications
(337 citation statements)
references
References 15 publications
15
301
8
2
Order By: Relevance
“…Combining this information with the data of the stable carbon isotopes, our results suggest that porpoises of North Norway/Barents Sea feed more offshore, and porpoises of the Southwest Coast feed more in coastal waters. Previous studies have reported that coastal regions seem to be more polluted than oceanic waters (Kannan et al, 2001a;Van de Vijver et al, 2003a). The new data presented on perfluorinated chemicals around the coasts of Norway seem to confirm such a pollution gradient.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Combining this information with the data of the stable carbon isotopes, our results suggest that porpoises of North Norway/Barents Sea feed more offshore, and porpoises of the Southwest Coast feed more in coastal waters. Previous studies have reported that coastal regions seem to be more polluted than oceanic waters (Kannan et al, 2001a;Van de Vijver et al, 2003a). The new data presented on perfluorinated chemicals around the coasts of Norway seem to confirm such a pollution gradient.…”
supporting
confidence: 59%
“…In recent years, a growing concern has been expressed about another class of organohalogen chemicals, namely perfluorinated organic compounds (FOCs). Results of previous studies suggest that perfluorochemicals, in particular, perfluorooctane sulfonic acid (PFOS), are spread worldwide in wildlife and in humans (Giesy and Kannan, 2001;Kannan et al, 2001aKannan et al, ,b, 2002Olsen et al, 1999). Even in remote arctic areas such as the Arctic Ocean, a detectable amount of fluorinated organochemicals could be quantified in the blood or organs, such as liver and kidney, of wildlife (e.g.…”
mentioning
confidence: 99%
“…PFOS is chemically and thermally stable, and is considered to be the terminal degradation product of many perfluorochemicals (PFCs) (Development, 2002). Considerable concentrations of PFOS have been detected in wildlife (Kannan et al, 2001;Wang et al, 2008) and humans (Kannan et al, 2004;Yeung et al, 2006). Owing to the potential bioaccumulation and the possible negative impact on the total environment and ultimately humans (Beach et al, 2006), understanding the pathway and investigating the environmental fate of PFOS are urgent.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the information on the contamination by PFCs is from biological samples collected in North America and Western Europe (2,15). Little is known about the current status and temporal trend of PFC contamination in Russia.…”
Section: Introductionmentioning
confidence: 99%